Evaluation of the Design of Civil Service in Public Institutions - Domingos Rodrigues Pereira (CV. Ulil Albab Corp, 2024)
The purpose of this study was to find out: Development of Service Professionals in Public Institutions, to find out the analysis and description of the Development of Service Professionals through the theory used as: Management, Administration, Evaluation, Design and Discipline. This study uses a qualitative approach to describe the phenomenon that has been studied clearly and systematically this study is used in text because this study aims to conduct a literature analysis study on the Design of Staff in Public Institutions. The findings identified in this literature research are that the decree-law on civil service in article 3 states that the design assessment also mentions several points regarding the motivation of the employee's work should be changed not about the salary scale of the civil servant in the table of salary of the geral regime, because the scale at which the implementation of the performance assessment every two years removes the scale with a small amount of non-market conditions, the conclusion is that the public institution is asked to give a view or recommendation to the public service to improve the scale of the staff, so that the staff can carry out their duties in accordance with the system.